Corporate reputation: An alternative measurement and empirical tests of the realtionship with financial performance in the Malaysian banking industry - Dwi Sunu Kanto, Slamet Widodo (Universiti Malaysia Sarawak (UNIMAS), 2013)
This thesis introduces and tests a new framework to identify the factors of corporate reputation and to explicate the relationship between corporate reputation and financial performance. The framework is built on the tenets of (1) Influences of the Malaysian context to identify the factors of corporate reputation and (2) Model of reputation-financial performance dynamics to explicate the relationship between corporate reputation and financial performance. Examination of these relationships, relationships between corporate reputation with its factors and with prior and current financial performance, provides a basis for delineating the process by which corporate reputation potentially generates superior financial performance for a company. These issues were explored in three studies (Study 1, 2, and 3) by surveying the stakeholders’ evaluation of the companies’ reputation and performance. Study 1 was a qualitative research to identify the factors of corporate reputation within the Malaysian context. These results were then used to conduct an exploratory quantitative study (Study 2) and a confirmatory factor analysis (Study 3) to determine the dimensionality of the factors of corporate reputation. Several structural models were then produced to test the relationships between corporate reputation and prior financial performance, as well as, current financial performance. A more critical structural model test using mediation analysis was also examined to determine the role of corporate reputation in the relationship between prior and current financial performance.